Increasing Community Participation in the Supervision of Regional Head Elections in Balamoa Village, Pangkah District, Tegal Regency in 2024 - Sutjiatmi, Sri; Suparto, Diryo; Widodo, Agus Setio; Adilla, Annisa; Afisa, Afisa (ASEAN Journal of Empowering Community, 2024)
The general election of regional heads as one of the manifestations of democracy is one of the national agendas that requires serious attention from various parties. Community participation in making this event a success is something that should not be ignored. One form of community participation is to supervise the election process. Effective participatory supervision is expected to be able to realize quality regional elections, so that the leaders produced really meet the expectations of the entire community.To increase community participation in the supervision of elections, the faculty of social and political sciences of Pancasakti Tegal University conducted community service in Balamoa Village, Pangkah Tegal District, which was attended by community leaders, village officials, using the method of lectures and discussions.The result of this community service activity is the awareness and determination of the Balamoa Community to supervise the election process in Tegal Regency, marked by a statement of attitude in the form of an integrity pact to realize safe, peaceful and quality elections.